Forças em luta para invenção de uma dança: política cultural e dança contemporânea em São Paulo - Cerqueira, Joana dos Santos Egypto de (2015)
This work presents three different movements characterized by disjunctive series interweaved around the genealogy of forces in struggle, composing the invention of a dance. It is especially inspired in the writings of Friedrich Nietzsche, Michel Foucault, Gilles Deleuze and Félix Guattari. Traces of what is considered as contemporary dance‟ are situated through the discussions around dance‟s execution by history and becomings that are installed on it. Therefore, the emergence of the Programa Municipal de Fomento à Dança (Municipal Dance Foster Programme) for the city of São Paulo is investigated, from ways of conducts taken out by performance artists during the passage of the 20th to the 21st century. The Vocational Programme (Programa Vocacional) is analised as one of the most important complementary political program related to the activity of artists from different fields. In this way, the research concentrates on the historical analysis of the cultural policies investments in Brazil that reflects in adjustments over the production of the so-called intangible materials‟ and controls related to the recent field of the creative economy . The government of conducts affects the life of artists and dancers in São Paulo, while the sophistication of power technologies develop calculations and create forms of selectivity around the current artistic creations in contemporary dance by means of governmental notices and tenders. Different ideas of culture‟ are presented based especially on nietzschean lectures about cultivation of social and ethical practices. A path of the development of cultures of the self through the experimentation of dances produced in São Paulo between the final decades of the 20th century and the beginning of the 21st raising mixes with a distant archipelago: Japan. That meeting is considered as one of the possible links that calls our attention for the political condition of the contemporary dance in São Paulo